A Dynamic Mobile Convergence based Resource Allocation Optical Network-Long Term Evolution (Dmcrapon-Lte) Technique for Optical Wireless Converged Networks - Abhishek Gaur, Dr. Priestly Shan, Dr. Sibaram Khara (International Journal of Advanced Science and Technology, 2020)
In recent times the demand for Quality of Services (QoS) requirements for end user applications has raised steeply due to bandwidth requirements, nature of the content and delay sensitivity of services. The Long Term Evaluation (LTE) is one such standard which is capable of addressing the increasing demand of mobile users. A main problem in an LTE is associated with the allocation of resource channel for the users in the network environment where the influence of unreliable resource allocation might result in the increase of interference among the users. This paper proposes a Dynamic Mobile Convergence Based Resource Allocation (DMCRAPON-LTE) technique that allows LTE radio access network for allocation of radio resources to the users in Resource Blocks (RB) efficiently with lesser average and maximum delay. The results taken from the simulation prove that the proposed DMCRAPON-LTE technique is better as compared to the existing integration architectures and it delivers an improved QoS to the end user.